Hb Jishui [HBA1: c.225C>G, Codon 74 (GAC>GAG), Asp→Glu]: A Novel α Chain Hemoglobin Variant Detected During Hb A1c Measurement. (4th July 2021) - Xie, Weijie; Zheng, Huiqi; Xu, Anping; Ji, Ling
Abstract: Here we report a novel α chain hemoglobin (Hb) variant found in a 74-year-old Chinese male. We accidentally discovered this Hb variant during the measurement of Hb A1c by a capillary electrophoresis (CE) method (Hb A1c program, CapillaryS3 TERA). However, Hb analysis with the Hb program of CapillaryS3 TERA and the VARIANT II™ β-Thalassemia Short Program showed no indication of the Hb variant. Sanger sequencing revealed a new missense mutation on the HBA1 gene [ HBA1 : c.225C>G, codon 74 (GA C >GA G ), Asp→Glu]. We named it Hb Jishui after the birthplace of the proband.